The Effect of Perceived Quality and Brand Awareness on Purchase Intention Mediated by Brand Trust in Tropicana Slim Products - Mauretta, Madeline; Marisa Muzammil, Oktafalia; Andri Yulius Caesar, Leo (Siber International Journal of Digital Business (SIJDB), 2024)
This study aims to determine the effect of perceived quality, brand awareness, and brand trust on buying interest in Tropicana Slim consumers. This study uses a population, namely Tropicana Slim consumers who live in DKI Jakarta and a sample with the criteria of knowing the Tropicana Slim brand and have never bought Tropicana Slim products, live in DKI Jakarta, and are at least 15 years old. The data in this study were processed using the SPSS version 25 application. This study used a sample of 100 respondents who were Tropicana Slim consumers. The results of hypothesis testing with the t-test explain that partially perceived quality and brand awareness have a positive and significant effect on brand trust and brand awareness has a positive and significant effect on purchase intention. Meanwhile, perceived quality and brand trust have no significant effect on purchase intention. Then in the sobel test results perceived quality and brand awareness have a negative and no significant effect on purchase intention mediated by brand trust.